Isolation of osteogenic progenitors from human amniotic fluid using a single step culture protocol - Ivana Antonucci; Irene Iezzi; Elisena Morizio; F Mastrangelo; Andrea Pantalone; Monica Mattioli‐Belmonte; Antonio Gigante; Vincenzo Salini; Giuseppe Calabrese; Stefano Tetè; Giandomenico Palka; Liborio Stuppia (2009)
Abstract Background Stem cells isolated from amniotic fluid are known to be able to differentiate into different cells types, being thus considered as a potential tool for cellular therapy of different human diseases. In the present study, we report a novel single step protocol for the osteoblastic differentiation of human amniotic fluid cells. Results The described protocol is able to provide osteoblastic cells producing nodules of calcium mineralization within 18 days from withdrawal of amniotic fluid samples. These cells display a complete expression of osteogenic markers (COL1, ONC, OPN, OCN, OPG, BSP, Runx2) within 30 days from withdrawal. In order to test the ability of these cells to proliferate on surfaces commonly used in oral osteointegrated implantology, we carried out cultures onto different test disks, namely smooth copper, machined titanium and Sandblasted and Acid Etching titanium (SLA titanium). Electron microscopy analysis evidenced the best cell growth on this latter surface. Conclusion The described protocol provides an efficient and time-saving tool for the production of osteogenic cells from amniotic fluid that in the future could be used in oral osteointegrated implantology.